Nazariah al-adab al-Islami baina al-udaba' al-Arab wa al-Malayuwiyyin - Yaacob, Adli (2014)
This article focuses on the idea of Islamic Literature which began in the Arab world through the writings of Muhammad Qutb, Syed Qutb, Najib al-Kilani, Emaduddin Khalil and a few others who came after them, influenced by their ideas. Later, concepts or theories of Islamic Literature began to take shape among the writers. In Malaysia, the concept was presented by Syed Muhammad Naquib Al-‘Attas who said that a writer must have a balanced views in the soul, body and mind. After him, there was Affandi Hassan who came up with something unconventional on the theory of Islamic literature. A number of other writers also tried to conceptualize the Islamic literature such as Shafie Abu Bakar, Kamala, ‘Ali Ahmad, Uthman el-Muhammady and Muhammad Kamal Hasan who tried to come up with the realistic view on Islamic literature based on what was suggested by another writer, Shahnon Ahmad. Another scholar, Kasssim Ahmad tried to dwell on the issue of methodology in Islamic literature. Ismail Ibrahim, another scholar, suggested that Islamic literature must stand on the principle of the unity of God (tawheed). This paper intends to study the concept of Islamic Literature and its development among the Arab and Malay writers. A comparative study on the similarities and differences of these concepts will also be a focus. Keywords: Islamic Literature, concept, differences, similarities